The Dilemma of People's Sovereignty in The Party System: A Constitutional Analysis of Political Party Domination - Auliya Khasanofa; Harmoko Harmoko; Byun Hae-Cheol (Universitas Muhammadiyah Purwokerto, 2026)
This study aims to analyze the dilemma of implementing popular sovereignty within Indonesia’s party system from the perspective of the 1945 Constitution and to examine the impact of political party dominance on the principle of popular sovereignty in constitutional democracy. This research employs a normative legal method using statutory and conceptual approaches to examine relevant legal norms, constitutional principles, and doctrines. The findings indicate that the implementation of popular sovereignty faces structural tension between constitutional norms and political practice. Although the 1945 Constitution affirms that sovereignty resides in the people, the election of members of the House of Representatives is fully mediated by political parties as the sole participants in elections. This dominance is further strengthened by parties’ administrative authority, particularly through the Interim Replacement (PAW) mechanism, which allows parties to replace legislators based on internal considerations such as political loyalty, organizational conflicts, or elite interests. As a result, the electoral mandate granted by voters may be overridden by party decisions, creating a conflict between popular legitimacy and party power. The study concludes that party dominance in candidate selection, faction discipline, and control over legislative positions reinforces a party-centered democracy model that weakens substantive representation and the direct relationship between representatives and constituents. therefore, limiting party authority in the PAW mechanism, strengthening a more voter-responsive representation system, and reforming internal party governance to ensure greater democracy and accountability are necessary. the novelty of this study lies in conceptualizing PAW not merely as an administrative mechanism but as a constitutional issue that potentially severs the people’s electoral mandate.